Kinerja Portofolio Saham pada Perusahaan Makanan, Property dan Pertambangan di Bursa Efek Indonesia - Nasri Zarman (Faculty of Economic and Business, 2017)
The Stock Portfolios' Performance of Food, Property, and Mining IndustryThis research aimed to analyze the Portfolio's performance of food industry, property, and mining. There are three parameters, namely: Sharpe Performance, Traynor Performance, and Jensen Performance. The three performance measurements assume that there is a linear connection between the return portfolios with the return of some market index. During the period, 2009 to 2013, and the mining and gas sub-sector are more productive than the other sub-sectors. The mining sector is better than the Property Sector and the Food Sector. Then based on the method of Jensen ALPHA it showed the highest performance group of mining stocks, in proportion to the risk which is also very high. The study suggests that the existing has to be maintained and further improved so that the mission to develop sources of potential energy into a profitable investment portfolio can sustain.DOI: 10.15408/ess.v7i2.5354